106k views
1 vote
Solving polynomial(2y-4)(3y+6)​

User Razor
by
5.2k points

2 Answers

4 votes


\Large{ \boxed{ \rm{ \red{To \: solve?}}}}

  • (2y - 4)(3y + 6)

Solution:-

⇛ (2y - 4)(3y + 6)

⇛ 2y(3y + 6) - 4(3y + 6)

⇛ 6y² + 12y - 12y - 24

⇛ 6y² - 24

☃️ So, Final answer = 6y² - 24

User Michael Erickson
by
5.3k points
3 votes

Answer:

6y² - 24

Explanation:

Expand. Follow FOIL method. FOIL =

First

Outside

Inside

Last.

First, multiply the first term of each parenthesis:

2y * 3y = 6y²

Next, multiply the outside terms from both parenthesis:

2y * 6 = 12y

Then, multiply the inside terms from both parenthesis:

-4 * 3y = -12y

Finally, multiply the last terms of each parenthesis:

-4 * 6 = -24

Combine like terms:

6y² + 12y - 12y - 24

6y² + (12y - 12y) - 24

6y² - 24

6y² - 24 is your answer.

~

User Hoa
by
5.3k points